A Comparative Study of Single-Event-Burnout for 4H-SiC UMOSFET - Ying Wang; Jian-cheng Zhou; Mao Lin; Xing-ji Li; Jian-Qun Yang; Fei Cao (IEEE Journal of the Electron Devices Society, 2022)
SiC UMOSFET is a kind of significant power device in the supply of aerospace. But it is sensitive to space radiation. In this paper, the discrepancy of SEB behavior and research of 4H-SiC UMOSFET with the different values of particle linear energy transfer (LET) are proposed and investigated by the 2D numerical simulations. And the improved MOSFET with multi-Buff was compared with the conventional UMOSFET. At last, simulation results demonstrated that under high-intensity radiation environment (high LET value heavy ion incidence), the proposed UMOSFET could increase the single-event burnout (SEB) hardness, and using the lattice temperature of device as the SEB behavior characterization of the SiC UMOSFET after heavy ion incidence is more reasonable and accurate than only using high steady-state drain current.